INNOVATIVE APPROACHES TO FORMATION OF LIFE RESILIENCE IN COMMUNITY (Psychology Travelogs, 2025)
The article presents the features of the formation of individual resilience in modern Ukrainian society. A detailed analysis of the phenomena, components and factors of the formation of stress resistance and resilience is presented. Theoretical approaches to the formation of individual resilience are considered.The formation of resilience as the ability to withstand, not break down, when facing life's adversities is important in today's realities. The destructive consequences of a long war, human losses, unemployment, forced displacement of the population lead to stress, negative psychological states in people, a decrease in the resilience index. In conditions of martial law, a person's resilience contributes to the preservation of mental health and productive activity in the community.The main goal of implementing a comprehensive psychosocial service to form resilience is the great need for socio-psychological support for the population to reduce the overall level of stress and anxiety, develop skills for first psychological aid, teach stress tolerance and prevent psychological trauma. The study of individual resilience as a psychological resource of the individual is an important direction of modern psychological and social research. Resilience is considered the main functional component of resilience, which maintains the stability of the personality system, a system-forming factor that sets the parameters of the main components of resilience. The focus of the research is to ananlyze innovative approaches to providing social services of resilience formation through the creation and functioning of Life Resilience Centres in the community.
Keywords: stress tolerance; resilience; social sphere; socio-psychological support; social service; mental health; resilience index; quality of life